Current Issues of Project Management Office at PT Solusi Telecom - Rendy Cahyadi; Aries Firman (AIBPM Publisher, 2020)
This qualitative research is conducted to discover which PMO model is suitable for Solusi Telecom, an Indonesian based telecommunication operator. The study identifies that desirable PMO should be able to: integrate corporate portfolio, standardize project management methodology, rollout project management tools, improve communication, grant complete oversight, and empower PMO leadership. Analysis on the suitable PMO model is conducted by using PMO Maturity Cube theoretical framework as a basis, which shows the suitable PMO model for Solusi Telecom is corporate scope and the combination of three roles: operational, strategic, and tactical with varying maturity level for each role. By applying this model, it is expected that the project performance is increased, which may increase revenue generation capability and improve employee productivity.